New genus and two new species of gelechiid moths (Lepidoptera, Gelechiidae) from Malaysia and Indonesia - Ponomarenko, Margarita G.; Omelko, Мichail M. (Zootaxa, 2025)
A new genus Mercedula gen. nov. and two new species (M. fuscomarginata sp. nov., type species, and M. storozhenkoi sp. nov.) are described and illustrated from Sabah, East Malaysia, and North Sumatra, Indonesia. The taxonomic position of the new genus within the family Gelechiidae is discussed.